Aortic haemostasis and resuscitation: advanced resuscitative endovascular balloon occlusion of the aorta for non-compressible torso haemorrhage and reversal of haemorrhage-induced traumatic cardiac arrest in a swine model - Barnard, Edward Benjamin Graham (2018)
Trauma is the leading cause of death in young people in the UK and US. Non-compressible torso haemorrhage (NCTH) is a major cause of potentially survivable trauma death. A large proportion of these patients are in traumatic cardiac arrest (TCA) on arrival at hospital, and survival rates after haemorrhagic TCA are extremely low. The limited data available suggest that closed chest compressions (CPR) are ineffective, and may be harmful, in haemorrhagic TCA. Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) has shown promise in the setting of NCTH, although its utility in haemorrhagic TCA is unknown. Selective Aortic Arch Perfusion (SAAP) is an experimental intervention that has the potential to resuscitate haemorrhagic TCA, but it has not been compared to CPR or REBOA. The aim of this research was to evaluate SAAP against other interventions for the management of haemorrhagic TCA.